Integrating Zakat and Waqf for Sustainable Food Security: An Islamic Social Finance Perspective from Indonesia - Mohamad Ainun Najib; Efy Setiawati Atanjuani; Nurul Fadhilah (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2026)
This study examines food security as a systemic and institutional issue and analyzes the role of Islamic social finance, particularly zakat and waqf, as an integrated solution within the Indonesian context. This research employs a qualitative approach based on library research using food systems and institutional economics perspectives. The analysis draws upon classical and contemporary literature on food security, zakat, and waqf relevant to Indonesia. The study finds that food insecurity in Indonesia is primarily driven by unequal access, institutional weaknesses, and the limitations of market-based financing rather than by insufficient food production alone. Zakat functions as a social protection instrument that safeguards food access and consumption among vulnerable groups, while waqf serves as a long-term asset-based financing mechanism that supports food production, stability, and sustainability. Therefore, sustainable food security cannot be achieved through zakat or waqf independently, but rather through their institutional integration. This study reconceptualizes Islamic social finance from a philanthropic approach into a strategic institutional framework for sustainable food security.